Impact of university teachers’ digital teaching skills on teaching quality in higher education - Jianyang Zhang; Yanran Wu (Cogent Education)
This study investigates the impact of digital teaching skills among university faculty on educational quality, focusing on how these skills affect teaching effectiveness within a digitized environment. Amidst the accelerating digital transformation, higher education has seen a shift in the role of university faculty from traditional lecturers to facilitators who incorporate various digital tools to enhance the educational experience. The research examines specific digital communication skills essential for improving instructional effectiveness in digital settings and explores the broader implications of digital literacy and resource quality on teaching outcomes. Findings suggest that adept use of digital tools not only enhances interactivity and student engagement but also addresses the challenges posed by digital divides and uneven access to technological resources. This study contributes to the understanding of digital transformations in higher education and provides insights into developing faculty competencies that align with modern educational demands.